2011
DOI: 10.1038/ng.835
|View full text |Cite|
|
Sign up to set email alerts
|

Exome sequencing in sporadic autism spectrum disorders identifies severe de novo mutations

Abstract: Evidence for the etiology of autism spectrum disorders (ASD) has consistently pointed to a strong genetic component complicated by substantial locus heterogeneity1,2. We sequenced the exomes of 20 sporadic cases of ASD and their parents, reasoning that these families would be enriched for de novo mutations of major effect. We identified 21 de novo mutations, of which 11 were protein-altering. Protein-altering mutations were significantly enriched for changes at highly conserved residues. We identified potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
928
2
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,081 publications
(985 citation statements)
references
References 51 publications
35
928
2
9
Order By: Relevance
“…Using NGS, O'Rack et al. identified de novo variations in FOXP1 , GRIN2B , SCN1A , LAMC3, and rare inherited CNTNAP2 variations (De Rubeis et al., 2014; O'Roak et al., 2011). Three genes were found in ASD probands with two de novo variations in each of these genes: BRCA2 , FAT1, and KCNMA1 (Neale et al., 2012).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Using NGS, O'Rack et al. identified de novo variations in FOXP1 , GRIN2B , SCN1A , LAMC3, and rare inherited CNTNAP2 variations (De Rubeis et al., 2014; O'Roak et al., 2011). Three genes were found in ASD probands with two de novo variations in each of these genes: BRCA2 , FAT1, and KCNMA1 (Neale et al., 2012).…”
Section: Reviewmentioning
confidence: 99%
“…Others genes encoding synaptic proteins linked to ASD were also identified by NGS: They include the glutamate receptors (GRIK2, GRIA3), the cell adhesion molecule CNTNAP2, and the scaffolding protein SHANK3. SHANK3 is involved in (i) synapse formation and maturation, (ii) the link between neurotransmitter receptors and ion channels, and (iii) the interaction with scaffolding proteins and gene regulatory proteins (e.g., protein of chromatin remodeling CHD8; Anney et al., 2010; Cotney et al., 2015; De Rubeis et al., 2014; O'Roak et al., 2011). NRXN1 , NLGN3/4X, and SHANK3 genes, which encode proteins involved in neuronal cell adhesion and in the regulation of synaptic transmission, are considered strong candidate loci for ASD (Weiss & Arking, 2009).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, other patients have been identified with chromosomal rearrangements affecting multiple genes including CNTNAP2, which are likely to confound the effects resulting from CNTNAP2 mutation [3][4][5][6][7][8][9] (Table 1). However, patients carrying point mutations or microdeletions that affect only the CNTNAP2 locus have now been reported, which provides insight into the deficit caused specifically by reduction or loss of CNTNAP2; [10][11][12][13][14][15][16] (Table 1).…”
Section: Cntnap2 and Cognitive Disorders Mutations Of Cntnap2mentioning
confidence: 99%
“…Research investigations using Genome Wide Association Study (GWAS) (Network and Pathway Analysis Subgroup of the Psychiatric Genomics Consortium, 2015; Wood, 2013), exome‐based sequencing (Girard et al, 2011; Iossifov et al, 2012; O'Roak et al, 2011; Vissers et al, 2010; Xu et al, 2012), and whole genome sequencing (Kong et al, 2012) techniques have revealed several candidate genes that are associated with common neuropsychiatric disorders such as Autism Spectrum Disorder (ASD), intellectual disability, and schizophrenia. However, in the case of rare disorders, understanding the genetic origins and progressions of disorders—one of the key objectives of Precision Medicine research (Collins & Varmus, 2015; Kohane, 2015; Kohane, Churchill, & Murphy, 2012)—is hindered by small patient population size, the consequent paucity of patient data, and the lack of robust phenotyping protocols (Baynam et al, 2015; Delude, 2015; Robinson, Mungall, & Haendel, 2015).…”
Section: Introductionmentioning
confidence: 99%